ANALISIS KUALITAS PELAYANAN DAN SUASANA CAFE TERHADAP LOYALITAS KONSUMEN DENGANKEPUASAN KONSUMEN SEBAGAI VARIABELINTERVENINGPADA CAFE ANAK PANTAI DI BONDOWOSO - Zarkasih, Zarkasih; Soeliha, Siti; Pramesthi, Riska Ayu (Fakultas Ekonomi dan Bisnis, 2023)
Marketing plays a crucial role in company management and is an essential factor as it directly impacts the success of the company in achieving its business objectives. This study aims to analyze the relationship between service quality and cafe ambience with customer loyalty, with customer satisfaction as an intervening variable, at Anak Pantai Cafe in Bondowoso. The sampling method is determined using quota sampling. Data analysis and hypothesis testing in this study are conducted using the Structural Equation Model - Partial Least Square (PLS-SEM). From the results of hypothesis testing using Smart PLS 3.0 application, it was found that service quality has a positive and significant impact on customer satisfaction, as well as cafe ambience, which also has a positive and significant impact on customer satisfaction. Furthermore, service quality also has a positive and significant influence on customer loyalty, as well as cafe ambience, which has a positive and significant impact on customer loyalty. Customer satisfaction itself also has a positive and significant influence on customer loyalty. Additionally, service quality has a positive and significant impact on customer loyalty through customer satisfaction, and the same is observed for Cafe ambience, showing a positive and significant impact on customer loyalty through customer satisfaction.